Lags in phenological acclimation of mountain grasslands after recent warming. (27th July 2021) - Bektaş, Billur; Thuiller, Wilfried; Saillard, Amelie; Choler, Philippe; Renaud, Julien; Colace, Marie‐Pascale; Della Vedova, Raphael; Münkemüller, Tamara
Abstract: In the current biodiversity crisis, one of the crucial questions is how quickly plant communities can acclimate to climate warming and longer growing seasons to buffer the impairment of community functioning. Answering this question is pivotal especially for mountain grasslands that experience harsh conditions but provide essential ecosystem services to people. We conducted a reciprocal transplant experiment along an elevation gradient (1, 920 m vs. 2, 450 m) in the French Alps to test the ability of plant species and communities to acclimate to warming and cooling. For 3 years, we measured weekly the timing of phenological events (e.g. start of flowering or greening) and the length of phenological stages linked to demographic performance (e.g. lengths of flowering or greening periods). We found that warming (and cooling) changed the timing of phenological events strongly enough to result in complete acclimation for graminoids, for communities in early and mid‐season, but not at all for forbs. For example, warming resulted in later greening of communities and delayed all phenophases of graminoids. Lengths of phenological stages did not respond strongly enough to climate change to acclimate completely, except for graminoids. For example, warming led to an acclimation lag in the community's yearly productivity and had a strong negative impact on flowering of forbs. Overall, when there was an acclimation failure, responses to cooling were mostly symmetric and confirmed slow acclimation in mountain grasslands. Synthesis . Our study highlights that phenological plasticity cannot prevent disruption of community functioning under climate warming in the short term. The failures to acclimate after 3 years of warming signals that species and communities underperform and are probably at high risk of being replaced by locally better‐adapted plants. Abstract : Our study highlights that phenological plasticity cannot prevent disruption of community functioning under climate warming in the short term. The failures to acclimate after 3 years of warming signals that species and communities underperform and are probably at high risk of being replaced by locally better‐adapted plants.